A Molecular View of Lipid Nanoparticles: Insights into their Morphology and Structural Plasticity - Porte, Sudha; Vadhana, V.; Sengupta, Durba (Small, 2025)
Lipid nanoparticles (LNPs) have emerged as versatile delivery vehicles for nucleic acid-based therapeutics. Despite their increasing importance, the molecular structure and physico-chemical characteristics of LNPs still remain unclear. In this review, the structural features and phase behavior of LNPs are highlighted. First, the various compositional elements, such as cationic lipids, helper lipids and sterols are discussed, illustrating their functional roles in the self-assembly and stability of LNPs. Molecular models derived from experimental and computational approaches are discussed to provide insights into the structural organization of the LNP components. The influence of sterols and helper lipids in modulating LNP architectures, including membrane fluidity and phase separation, which are key factors for both fusion potential and endosomal escape, is discussed. Variations in sterol content and headgroup chemistry can induce transitions from lamellar to non-lamellar structures, thereby influencing gene transfection outcomes. Further, how cationic lipids induce structural phase transitions, such as lamellar-to-hexagonal and inverse cubic rearrangements under physiological and acidic pH, mimicking extracellular and endosomal conditions, are described. These transitions play a pivotal role in ribonucleic acid (RNA) release and membrane fusion events. This comprehensive review allows to reconcile molecular and structural dynamics that would be necessary for rational design of RNA delivery systems.
Keywords: drug delivery; lipid nanoparticles; phase separation; vaccine delivery